A study of Cyclonicity in relation to rainfall over Indian region - TRIPATHI, N. (MAUSAM, 1963)
Based on examination of daily synoptic charts for the ten year period, 1944-1953, a study has been made of days on which centre of a cyclonic system lay in each five degree square in the region covering India and neighbourhood. Monthly charts have been prepared, showing frequency of occurrence of cyclonicity over each such zone and also its progressive behaviour in regard to its persistence or future movement. A rainy day, defined as one having rainfall of 10cents or more, is found to be related significantly to cyclonicity over a given area except durung hot weather period, March to May.